Small radius electron and hole polarons in PbX2 (X = F, Cl, Br) crystals: a computational study. Issue 46 (10th November 2021) - Mastrikov, Yu. A.; Chuklina, N. G.; Sokolov, M. N.; Popov, A. I.; Gryaznov, D. V.; Kotomin, E. A.; Maier, J.
Abstract : Predicted by Landau in 1933, the self-trapped electron in PbCl2, for the first time was experimentally detected by Nistor et al . and Hirota et al . in 1993, and computationally modelled by Mastrikov et al . in 2021. Abstract : First-principles hybrid density functional theory (DFT) calculations were performed for small radius polarons – self-trapped electrons (STELs) and holes (STHs) in Pb X 2 ( X = F, Cl, Br) crystals, widely used as parent materials for inorganic halide perovskites (CsPb X 3 ) and scintillators. The atomic and electronic structures, spin and charge distributions and formation energies for both types of polarons were predicted for orthorhombic PbF2 and STELs for cubic PbF2 . The STH structure was identified in a controversial case of PbCl2 . We also confirmed and analyzed in detail experimentally suggested configurations for other cases. It is shown how, due to a delicate balance of ionic and covalent chemical bonding, hole localization changes from a single cation in fluorides and chlorides to an anion dimer in bromides. The positions of STEL/STH energy levels in the band gap were determined and discussed in conjunction with the role of spin–orbit effects.